Diversity in Scientific Discovery. Issue 11 (November 2021) - Qureshi, Alia P.; Stain, Steven C.; Solomon, Naveenraj L.
Presented here is a brief discussion on the imperative need and thoughtful approaches to embracing diversity, equity and inclusion within scientific enquiry.